DINAMIKA JENIS Macaranga gigantea: DAMPAK DARI TEBANG PILIH DAN KEBAKARAN HUTAN DI KALIMANTAN TIMUR: Dynamics of Macaranga gigantea: Couple impact of selective logging and forest fire in East Kalimantan - Sutedjo Sutedjo; Paulus Matius; Rita Diana; Rohman Rohman (Fakultas Kehutanan Universitas Jambi, 2021)
The aim of the study is to analyze the dynamics of Macaranga gigantea for 12 years from 2005 to 2016. The indicator used is the Important Value Index (INP) which includes density, dominance and type frequency. Measurements on trees up to 10 cm in diameter, carried out on a permanent plot derived from light, heavy and medium cuts, with each sample plot covering an area of 3 ha. Identification has found 11 species of Macaranga spp. The species that dominates the highest INP is M. gigantea, followed by M. hypoleuca and M. triloba. The results of the analysis showed that Type M. gigantea had the highest number of individuals during 12 years of observation and that the presence of Type M. gigantea had reached the highest number in 10 years after fire disturbances. In addition, the type of M. gigantea present in forest research areas due to light logging is 2 (two) times more than heavy cutting because the heavy cutting of the area is very open to competition between species of pioneer plant.